Osimertinib as treatment for EGFR exon 20 insertion-positive lung adenocarcinoma - Murano, Chihiro; Igarashi, Akira; Yamauchi, Keiko; Inoue, Sumito; Watanabe, Masafumi (Technische Universität Dortmund, 2019)
A 20-year-old woman was diagnosed with stage 4 lung adenocarcinoma with an epidermal growth factor receptor (EGFR) exon 20 insertion gene mutation. Although the patient underwent chemotherapy, her lesions progressed. Liquid biopsy for EGFR T790M mutation showed negative results. After administering osimertinib, reduction of the lesions at the primary site was observed, and the patient’s respiratory condition improved. Previous reports showing successful treatment of EGFR exon 20 insertion-positive lung adenocarcinoma with the standard osimertinib dose of 80 mg are limited. The present case demonstrated that osimertinib could be a possible treatment option for EGFR exon 20 insertion-positive lung adenocarcinoma.
EXCLI Journal;Vol. 18. 2019, p.893-898
Keywords: Lung cancer; Adenocarcinoma; EGFR exon 20 insertion gene mutation; Osimertinib; 610